Effects of enzyme inducers efavirenz and tipranavir/ritonavir on the pharmacokinetics of the HIV integrase inhibitor dolutegravir - Song, Ivy; Borland, Julie; Chen, Shuguang; Guta, Phyllis; Lou, Yu; Wilfret, David; Wajima, Toshihiro; Savina, Paul; Peppercorn, Amanda; Castellino, Stephen; Wagner, David; Hosking, Louise; et al. (European journal of clinical pharmacology, 2014)
Purpose Dolutegravir (DTG) is an unboosted, integrase inhibitor for the treatment of HIV infection. Two studies evaluated the effects of efavirenz (EFV) and tipranavir/ritonavir (TPV/r) on DTG pharmacokinetics (PK) in healthy subjects. Methods The first study was an open-label crossover where 12 subjects received DTG 50 mg every 24 hours (q24h) for 5 days, followed by DTG 50 mg and EFV 600 mg q24h for 14 days. The second study was an open-label crossover where 18 subjects received DTG 50 mg q24h for 5 days followed by TPV/r 500/200 mg every 12 hours (q12h) for 7 days and then DTG 50 mg q24h and TPV/r 500/200 mg q12h for a further 5 days. Safety assessments and serial PK samples were collected. Non-compartmental PK analysis and geometric mean ratios and 90 % confidence intervals were generated. Results The combination of DTG with EFV or TPV/r was generally well tolerated. Four subjects discontinued the TPV/r study due to increases in alanine aminotransferase that were considered related to TPV/r. Co-administration with EFV resulted in decreases of 57, 39 and 75 % in DTG AUC (0– τ ) , C max and C τ , respectively. Co-administration with TPV/r resulted in decreases of 59, 46 and 76 % in DTG AUC (0– τ ) , C max and C τ , respectively. Conclusions Given the reductions in exposure and PK/pharmacodynamic relationships in phase II/III trials, DTG should be given at an increased dose of 50 mg twice daily when co-administered with EFV or TPV/r, and alternative regimens without inducers should be considered in integrase inhibitor-resistant patients.